Increased photoconductivity lifetimes in GaAs nanowires via n-type and p-type shell doping - Boland, J; Casadei, A; Tutuncouglu, G; Matteini, F; Davies, C; Gaveen, F; Amaduzzi, F; Joyce, H; Herz, L; Fontcuberta i Morral, A; Johnston, M (IEEE, 2016)
Reliable doping in GaAs nanowires is essential for the development of novel optoelectronic devices. Previously, GaAs nanowires have been shown to exhibit extremely short photoconductivity lifetimes of a few picoseconds due to their high surface recombination velocity, which is detrimental for nanowire devices, such as solar cells and nanowire lasers. Here, we show that, by exploiting engineered band-bending via selective doping, this parasitic surface recombination can be reduced. We utilise non-contact time-resolved terahertz spectroscopy to characterise the doping efficiency in n-type and p-type doped GaAs nanowire8 and show high carrier concentrations of the order of 1018 cm-3. The carrier lifetimes were increased by an order of magnitude from 0.13ns for undoped to 3.8ns and 2.5ns for n-doped and p-doped GaAs nanowires respectively; showing that surface recombination is greatly suppressed as a result of shell doping. We also present a novel effect of p-doping in GaAs nanowires: a rapid decay in photoconductivity within 25ps after photoexcitation. This fast decay is attributed to rapid electron trapping at the nanowire surface due to doping related band bending. Thus, we demonstrate the advantages of selective doping for enhancement of desirable transport properties in GaAs nanowires, as well as highlighting terahertz spectroscopy as a reliable technique for characterising doped GaAs nanowires1.